On Bicyclic T-Factorizability in the Class T[14, 6] - Petrenyuk, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We completely solve the problem of the existence of T-factorizations in the class of trees of order 14 with the largest vertex order 6.